A lethal engagement : a mystery - Skelly, AJ (Crooked Lane Books, 2025)
"1890. American heiress, Cora Beaumont is celebrating her engagement to Terrance Tristan, the second son of a duke. Their union will solidify Cora's place in British society and put her in a rare position of power, but as they embark on the Lady Air's maiden voyage to England, Cora soon finds that not everyone in society is accepting of her recent engagement, and tensions fly as high as the airship. When a body is discovered the first night on the ship, with a calling card for Cora on the victim, she's determined to find the killer hidden among the passengers before they come for her next. As Cora tries to solve the murder without attracting unsavory attention, her fiancé's wandering eye may cause even more problems for her position in society. Gossip travels fast aboard the airship and bad news could sink the Lady Air, as well as Cora's own social status, before they reach their final destination. When more bodies are discovered, Cora teams up with her soon-to-be brother-in-law, Nicholas, as they scour the ship for clues. If she fails, it won't only be her reputation visiting the undertaker." --